2019
DOI: 10.1038/s41562-019-0653-z
|View full text |Cite
|
Sign up to set email alerts
|

New alcohol-related genes suggest shared genetic mechanisms with neuropsychiatric disorders

Abstract: Excessive alcohol consumption is one of the main causes of death and disability worldwide. Alcohol consumption is a heritable complex trait. We conducted a meta-analysis of genome-wide association studies (GWAS) of gram/day (g/d) alcohol consumption in UK-Biobank, AlcGen and CHARGE+ consortia accumulating 480,842 people of European descent to decipher the genetic architecture of alcohol intake. We identified 46 novel, common loci, and investigated their potential functional significance using magnetic resonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
106
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(113 citation statements)
references
References 91 publications
6
106
1
Order By: Relevance
“…We integrated genomic and bioinformatic analyses which provided a rapid approach for filling the translational space between human and animal genetics research. Similar to other genetic studies of drug use 26-28 , these findings indicated a neuro-epigenetic component to the genetic inheritance of tobacco consumption, while also localizing genomic regions of interest. By using a genetic sample of over 100,000 humans and meta-analyzing across three species from seven gene expression studies, we found that approximately 4.2%-39.5% of the heritability for the frequency of human tobacco use can be attributed to mRNA readout related to nicotine exposure/consumption in the brain.…”
Section: Discussionsupporting
confidence: 82%
“…We integrated genomic and bioinformatic analyses which provided a rapid approach for filling the translational space between human and animal genetics research. Similar to other genetic studies of drug use 26-28 , these findings indicated a neuro-epigenetic component to the genetic inheritance of tobacco consumption, while also localizing genomic regions of interest. By using a genetic sample of over 100,000 humans and meta-analyzing across three species from seven gene expression studies, we found that approximately 4.2%-39.5% of the heritability for the frequency of human tobacco use can be attributed to mRNA readout related to nicotine exposure/consumption in the brain.…”
Section: Discussionsupporting
confidence: 82%
“…Previous work has shown that the genetic architecture of AUD (and PAU) differs substantially from that of alcohol consumption [24]. There have been larger studies of alcohol quantity-frequency measures [9, 36]; alcohol consumption data are available in many EHRs, thus they were included in many studies of other primary traits, like cardiac disease. AUD diagnoses are collected much less commonly.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, genetic variation of the XRCC5 gene is associated with intravenous EtOH self‐administration (Juraeva et al., ). The approach has been extended to a larger set of alcohol‐dependent humans and resulted in the identification of 46 novel loci for alcohol consumption (Evangelou et al., ). Together with functional studies, the results also suggest common genetic mechanisms with other neuropsychiatric disorders.…”
Section: Translation From Flies and Worms To Mammals And Vice Versamentioning
confidence: 99%